Resource loop for circular economy: hotel composting project - Ratkai, Melinda (Henry Stewart Talks, 2026)
This case study explores how Spanish hotel chain Garden Hotels & Resorts implemented a circular economy system. It is an example of how hotels can become environmental stewards without compromising guest experience or operational efficiency.